Do employer-sponsored health insurance schemes affect the utilisation of medically trained providers and out-of-pocket payments among ready-made garment workers? A case–control study in Bangladesh. Issue 3 (3rd March 2020) - Ahmed, Sayem; Sarker, Abdur Razzaque; Sultana, Marufa; Roth, Felix; Mahumud, Rashidul Alam; Kamruzzaman, Md; Hasan, Md Zahid; Mirelman, Andrew J.; Islam, Ziaul; Niessen, Louis W.; Rehnberg, Clas; Khan, AK Azad; et al.
Abstract : Objective: We estimated the effect of an employer-sponsored health insurance (ESHI) scheme on healthcare utilisation of medically trained providers and reduction of out-of-pocket (OOP) expenditure among ready-made garment (RMG) workers. Design: We used a case–control study design with cross-sectional preintervention and postintervention surveys. Settings: The study was conducted among workers of seven purposively selected RMG factories in Shafipur, Gazipur in Bangladesh. Participants: In total, 1924 RMG workers (480 from the insured and 482 from the uninsured, in each period) were surveyed from insured and uninsured RMG factories, respectively, in the preintervention (October 2013) and postintervention (April 2015) period. Interventions: We tested the effect of a pilot ESHI scheme which was implemented for 1 year. Outcome measures: The outcome measures were utilisation of medically trained providers and reduction of OOP expenditure among RMG workers. We estimated difference-in-difference (DiD) and applied two-part regression model to measure the association between healthcare utilisation, OOP payments and ESHI scheme membership while controlling for the socioeconomic characteristics of workers. Results: The ESHI scheme increased healthcare utilisation of medically trained providers by 26.1% (DiD=26.1; p<0.01) among insured workers compared with uninsured workers. While accounting for covariates, the effect on utilisation significantly reduced to 18.4% (p<0.05). The DiD estimate showed that OOP expenditure among insured workers decreased by −3700 Bangladeshi taka and -1100 Bangladeshi taka compared with uninsured workers when using healthcare services from medically trained providers or all provider respectively, although not significant. The multiple two-part models also reported similar results. Conclusion: The ESHI scheme significantly increased utilisation of medically trained providers among RMG workers. However, it has no significant effect on OOP expenditure. It can be recommended that an educational intervention be provided to RMG workers to improve their healthcare-seeking behaviours and increase their utilisation of ESHI-designated healthcare providers while keeping OOP payments low.